Respon Enzim Antioksidatif Sonchus oleraceus terhadap Cekaman Krom pada Media Tanam Berbeda - Sucahyo, Sucahyo; Kasmiyati, Sri (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTSonchus oleraceus is a weed that is capable of living in chromium contaminated environments, so their physiological, biochemical and molecular responses can be used as biomarkers of chromium stress. Changes in the activity of antioxidative enzymes can be used as a biomarker of biochemical against heavy metal stress.The objective of this research was to know the response of antioxidative enzymes activity in S. oleraceus subjected to Cr stress on different planting media. The research was done in 2 factors i.e. planting media types and Cr compound types (Cr3+and Cr6+). Parameters measured were antioxidative enzymes activity i.e catalase (CAT), ascorbate peroxidase (APX), superoxidase dismutase (SOD), and glutathion reductase (GR), dissolved protein content in leaves, and content of Cr6 + and Cr total in roots and shoots.The data were analyzed with a two way ANOVA using SAS 9.1 32-bit for windows. The results indicated that activity of antioxidative enzymes (CAT, APX, SOD and GR) of S. oleraceus leaves tend to increase under Cr stress condition. The Cr6+ treatment of 10 mg/L significantly increased the antioxidative enzyme activity of CAT, APX, SOD and GR in S. oleraceus leaves. The antioxidative enzyme activity (APX, SOD and GR) S. oleraceus grown on soil medium containing sludge was higher than that grown on soil media and on the mixture of sludge: soil (1: 1). Under Cr stress conditions, the roots and shoots of S. oleraceus grown on sterile sand media, soil and the mixture of sludge:soil (1:1) accumulate Cr6+ and Cr total. The accumulation of Cr6+ was found the highest in shoots, meanwhile accumulation of Cr total was found the highest in the roots. The Cr treatments and planting media also significantly influenced the soluble protein content in S. oleraceus leaves.Key words: antioxidant, oxidative stress, chromium, weed, soluble protein